PENGARUH KECEPATAN RELATIF PERMUKAAN GESEK DAN TEMPERATUR TERHADAP KOEFISIEN GESEK BLOK REM KOMPOSIT KERETA API - Triono, Agus (ROTOR, 2013)
Braking system is an important thing on safety of the train. In that process, kynetic energyÂ changed into thermal energy that would be known by the increasing of temperature at the surface and around the area of contact between the wheels and brakes. From research before, the increasing of contact temperature would lead a thermal crack on the wheel. Failure could be occure by that crack. Based on that results, research on the phenomenon of rising temperatures due to friction between wheel and railwould be very needed. In this paper,the effect of temperature and relative velocity of the surface to coefficient of friction would be studied. Experimental study of this paper using pin on disc test with 2 kg load and relative velocity variated from 4,61 m/s(400 rpm); 5,76 m/s(500 rpm) and 6,91 m/s(600 rpm).Results of this research shows that increasing temperature and relative velocity would lead an increasing of friction coefficient.Â Key word: brake, composite, temperature, friction coefficient, relative velocity